The Anti-Viral and Cognitive Enhancement Properties of Edible Bird's Nest: A Narrative Review - Yusnianingsih, Cuay (Bali Medical and Wellness Journal, 2024)
Background: Edible bird's nest has been used as a traditional Chinese medicine since the 7th century. It is rich in protein, carbohydrates, moisture, ash, and fat. Recent research has focused on its potential health benefits, such as anti-viral properties, cognitive enhancement, and roles as an immunomodulator and antioxidant. Objective: This review explores the anti-viral and cognitive enhancement properties of edible bird's nest. Methods: This review followed the PRISMA Scoping Review (PRISMA ScR) guidelines. Relevant studies were systematically identified using PubMed and Google Scholar with keywords such as "edible bird's nest," "anti-viral," "cognitive enhancer," and "Alzheimer's disease." In vitro and in vivo studies published in peer-reviewed journals that focused on the anti-viral and cognitive effects of edible bird's nest were included. Articles were initially screened through titles and abstracts, and relevant studies were reviewed in full to extract key data on study design, methods, and outcomes. Results: Edible bird's nest enhances cell functions by increasing the density and number of lysosomes, reducing Rab5 protein activity, enhancing mucin production, and modulating Rhoa expression, which regulates actin cytoskeleton dynamics. These mechanisms inhibit the attachment, endocytosis, maturation, and release of influenza A virus particles. As a cognitive enhancer, edible bird's nest significantly improves memory and neuroprotective functions by inhibiting neuroinflammatory processes and oxidative stress. Additionally, it may enhance mitochondrial function and increase the number of active mitochondria. Conclusion: Edible bird's nest demonstrates anti-viral and cognitive enhancement effects with no reported side effects in vitro and in vivo. Further research should aim at clinical trials to establish effective and optimal dosages.